Peran PP Al-Amanah dalam Pembentukan Sosio-Cultural Masyarakat Junwangi Sidoarjo - Ayunina Mahanani (Jurnal Al-Tatwir, 2020)
According to the preliminary study, Junwangi in Krian village is located in the suburb of Sidoarjo. The people of Junwangi make a living from the vast rice fields away from the city crowds. Such situation promotes the activity of illegal gambling and alcohol consumption which are transgressing the religious norms. These misdemeanors and criminal offenses tend to be overlooked since Junwangi is located in the less-monitored police areas. Moreover, there has not been any figure or leader in Junwangi, making these misdemeanors to continuously done and spread uncontrollably. The current study aims at analyzing Junwangi community’s opinions towards the importance of the role of Al-Amanah Islamic boarding school in establishing sociocultural community in the village. This study is descriptive qualitative research. The data was collected through interview, field study, and documentation. The informants of the study are the descent of the Kyai in Al- Amanah and the community around the Islamic boarding school. The result of this study showed that Al – Amanah as has a role in the formation of character through formal and informal education. Moreover, pesantren (Islamic boarding school) can contribute to the community by planting Islamic values through certain approaches so that one day the misdemeanors will subside.